Effects of the CarFreeMe Traumatic Injuries, a Community Mobility Group Intervention, to Increase Community Participation for People With Traumatic Injuries: A Randomized Controlled Trial With Crossover - George, Stacey; Barr, Christopher; Berndt, Angela; Milte, Rachel; Nussio, Amy; Adey-Wakeling, Zoe; Liddle, Jacki (Frontiers in Neurology, 2022)
Introduction After traumatic injuries community participation is a common goal, promoting wellbeing and independence. Community mobility and transportation influence an individual's independence in community participation. With the ability to drive safely often compromised after traumatic injuries, the adverse consequences of driving cessation include a loss of identity and reduced participation in chosen activities. In rehabilitation, individualized community mobility intervention is not routinely provided. The primary aim of this trial was to evaluate whether a group-based intervention, the CarFreeMe TI program was more effective than standard intervention, an information sheet of alternative transport, in improving community mobility for people following traumatic injuries. The secondary aim of this study was to evaluate the effect: types of transport used, transport satisfaction, community mobility self-efficacy, quality of life, goal satisfaction and performance, for people following traumatic injuries; and to undertake a preliminary assessment of the potential resource use associated with the intervention, and lessons for implementation. Design Prospective, pilot, randomized, blind observer, controlled trial with crossover. Participants Twenty individuals with traumatic injuries. Intervention Six-week group-based support and education program, the CarFreeMe TI delivered in community settings (intervention) and standard information related to transport options available (control). Primary Outcome Measures Community participation using a Global Positioning System device to record the location and number of outings from home. Secondary Outcome Measures CarFreeMe TI Transport Questionnaire, Community Mobility Self-efficacy Scale, quality of life measures, Modified Canadian Occupational Performance Measure for goals (importance and satisfaction), participant satisfaction survey results and researcher logs. Results Those who received the intervention were more likely to use public transport and transport services and had an improved quality of life, when compared to the control group. The intervention group also reported high levels of improvement in goal performance and satisfaction. Global Positioning System data collection was incomplete, with geolocation data unusable. There was no significant change in number/type of visits away from home. Conclusions A group-based community mobility education program promoted modes of active independent transport but did not impact on outings from home. Future research could include passive collection methods using a smartphone to record community participation. Clinical Trial Registration https://www.anzctr.org.au/, identifier: ACTRN12616001254482.